Back Cover: Pushing the Boundaries of Vinylogous Reactivity: Catalytic Enantioselective Mukaiyama Aldol Reactions of Highly Unsaturated 2‐Silyloxyindoles (Chem. Eur. J. 17/2015). Issue 17 (10th April 2015) - Curti, Claudio; Sartori, Andrea; Battistini, Lucia; Brindani, Nicoletta; Rassu, Gloria; Pelosi, Giorgio; Lodola, Alessio; Mor, Marco; Casiraghi, Giovanni; Zanardi, Franca
<x xml:space="preserve">Abstract</x> On the road to hypervinylogy. On a dark cloudy day, lightning strikes a straight road at a distant point on the horizon. This scene represents how various aldehydes add at the most distant ω‐point of the polyene chain of 3‐polyalkenyl‐2‐oxindole nucleophiles through a catalytic, hypervinylogous Mukaiyama aldol reaction, as described by C. Curti, F. Zanardi et al. in their Full Paper on page 6433 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>